2017
DOI: 10.17943/etku.322366
|View full text |Cite
|
Sign up to set email alerts
|

Di̇ji̇tal Hi̇kayeleme Yöntemi̇ İle Etki̇li̇ Türkçe Öğreti̇mi̇

Abstract: ÖzDijital hikayeleme, geçmişi yüzyıllara dayanan hikâye anlatımı ile çoklu ortam araçları birleştirilerek ortaya çıkmış bir kavramdır. Derslerde dijital hikayelerin etkili kullanımının teknoloji entegrasyonunu destekleyici bir rolü olabilmektedir. Bu noktadan hareketle bu çalışmada bilgi ve iletişim teknolojilerinden (BİT) yararlanılarak, Türkçe derslerinde kullanılmak üzere dijital hikayeleme yöntemine göre ders materyalleri (dijital hikayeler) hazırlanmıştır. Araştırma, geliştirilen dijital hikâyelerin kulla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 9 publications
0
5
0
6
Order By: Relevance
“…Regarding the use of digital stories in different classes, Yılmaz et al (2017) concluded that using the digital storytelling method in teaching Turkish has a significant effect on students' reading skills. Kahraman (2013), Büyükcengiz (2017, and Tunç Ayvaz (2016) emphasized the positive results of using the digital storytelling method in different courses.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the use of digital stories in different classes, Yılmaz et al (2017) concluded that using the digital storytelling method in teaching Turkish has a significant effect on students' reading skills. Kahraman (2013), Büyükcengiz (2017, and Tunç Ayvaz (2016) emphasized the positive results of using the digital storytelling method in different courses.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Baki and Feyzioglu (2017b: 689) stated that "the dynamic and powerful tool (digital stories) that covers many of today's generation's expectations has various advantages that will enable the student to enjoy knowledge with an understanding parallel to the constructivist approach's" learning by living "perspective. Moreover, the students who participated in the study of Yilmaz, Ustundag, Gunes, and Caliskan (2017) stated that the course will be fun with all the readings in the textbooks as digital stories. Torres, Ponca, and Pastor (2012) emphasize that digital stories increase students' level of interest and attention and that they are an educational tool for teachers.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…Beceri alanı (dinleme, okuma, yazma, dil bilgisi) moderatör değişkeni incelendiğinde, beceri alanları arasındaki varyansın Türkçe dil becerilerinin gelişimi açısından anlamlı olmaması dijital öykülerin bütün dil becerilerinin gelişimi üzerinde olumlu etkiye sahip olduğunu göstermektedir. Alanyazında yer alan ana dili ve yabancı dil eğitimine yönelik birçok çalışmada dijital öyküleme uygulamalarının veya araştırmacıların hazırladığı, öğrenme aracı olarak kullanılan dijital öykülerin konuşma (Abdolmanafi-Rokni ve Qarajeh, 2014; Tatlı ve Aksoy, 2017), dinleme (Abidin, Pour-Mohammadi, Souriyavongsa, Tiang ve Kim, 2011;Ciğerci, 2015;Demirbaş, 2019;Türe-Köse, 2019;Verdugo ve Belmonte, 2007), okuma (Adıgüzel ve Kumkale, 2018;Çiftçi, 2019;Özerbaş ve Öztürk, 2017;Şentürk-Leylek, 2018;Yılmaz, Üstündağ, Güneş ve Çalışkan, 2017), yazma (Baki, 2015(Baki, , 2019Balaman-Uçar, 2016;Çıralı, 2014;Dayan, 2017;Demirbaş, 2019;Duman ve Göçen, 2015;Gider, 2019;Gündüz, 2019;Uslu, 2019;Yamaç, 2015;Yılmaz vd., 2017) olmak üzere dil becerilerinin gelişiminin yanı sıra sözcük öğrenimi (Aitkuzhinova-Arslan, Gün ve Üstünel, 2016;Özer, 2016;Yardım, 2011) ve dil becerilerinin gelişimine temel oluşturan dil bilgisi öğretimi (Özkaya, 2017) üzerinde etkili olduğu tespit edilmiştir. Bu da dijital öykülerin bütün dil becerilerinin gelişimi üzerinde olumlu etkiye sahip olduğu sonucunu desteklemektedir.…”
Section: Tartışma Ve Sonuçunclassified